let V be Z_Module; :: thesis: for F being FinSequence of V st F is one-to-one holds
for L being Linear_Combination of V st Carrier L c= rng F holds
Sum (L (#) F) = Sum L

let F be FinSequence of V; :: thesis: ( F is one-to-one implies for L being Linear_Combination of V st Carrier L c= rng F holds
Sum (L (#) F) = Sum L )

assume A1: F is one-to-one ; :: thesis: for L being Linear_Combination of V st Carrier L c= rng F holds
Sum (L (#) F) = Sum L

rng F c= rng F ;
then reconsider X = rng F as Subset of (rng F) ;
let L be Linear_Combination of V; :: thesis: ( Carrier L c= rng F implies Sum (L (#) F) = Sum L )
assume A2: Carrier L c= rng F ; :: thesis: Sum (L (#) F) = Sum L
consider G being FinSequence of V such that
A3: G is one-to-one and
A4: rng G = Carrier L and
A5: Sum L = Sum (L (#) G) by VECTSP_6:def 6;
reconsider A = rng G as Subset of (rng F) by A2, A4;
set F1 = F - (A `);
X \ (A `) = X /\ ((A `) `) by SUBSET_1:13
.= A by XBOOLE_1:28 ;
then A6: rng (F - (A `)) = rng G by FINSEQ_3:65;
F - (A `) is one-to-one by ;
then A7: ex Q being Permutation of (dom G) st F - (A `) = G * Q by ;
reconsider F1 = F - (A `), F2 = F - A as FinSequence of V by FINSEQ_3:86;
A8: (rng F2) /\ (rng G) = ((rng F) \ (rng G)) /\ (rng G) by FINSEQ_3:65
.= {} by ;
ex P being Permutation of (dom F) st (F - (A `)) ^ (F - A) = F * P by FINSEQ_3:115;
then Sum (L (#) F) = Sum (L (#) (F1 ^ F2)) by Th5
.= Sum ((L (#) F1) ^ (L (#) F2)) by ZMODUL02:51
.= (Sum (L (#) F1)) + (Sum (L (#) F2)) by RLVECT_1:41
.= (Sum (L (#) F1)) + (0. V) by
.= (Sum (L (#) G)) + (0. V) by
.= Sum L by ;
hence Sum (L (#) F) = Sum L ; :: thesis: verum